Carcinoma Ex-Pleomorphic Adenoma Diagnosis During Global Health Engagement Operations. (25th January 2021) - Haltiner, Caitlin C; Betz, Sasha; Smith, Jenny; Nelson, Brenda; Ambrosio, Art A
ABSTRACT: Introduction: In global health engagement settings, performance of oncologic surgery is evaluated by understanding the host nation healthcare capacity to include inpatient care support and the available postoperative adjunctive therapy to include chemotherapy and radiation therapy. Materials and Methods: We present a case during Pacific Partnership 2018 of a patientwith a malignant facial mass diagnosed postoperatively. A literature review was conducted, searching specifically for cases related to pleomorphic adenoma (PA), carcinoma ex-PA, cases of misdiagnosis, and global health engagement operations. Results: The patient presented without constitutional symptoms, clinical lymphadenopathy, or cranial nerve VII weakness with a preoperative host nation diagnosis of a benign salivary neoplasm (PA). Postoperatively, a gross total resection of the mass was diagnosed as high-grade adenocarcinoma—a carcinoma ex-PA of the parotid gland. Oncologic staging was noted to be advanced at T3N0, and the patient was referred back to the host nation surgeons for radiation oncology consultation and clinical surveillance to follow. Discussion: Diagnosis of carcinoma ex-PA—a rare form of salivary gland malignancy—is not always straightforward because of its high degree of cellular heterogeneity, leading to inconsistencies in preoperative sampling results. This case addresses the preoperative diagnostic challenges associated with this type of malignancy, different types of possible treatment modalities aimed at reducing postoperative morbidity, and the preoperative and postoperative challenges that are critical to address during health engagement operations.